2021
DOI: 10.1111/and.14168
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic masturbation syndrome may be an important cause of erectile dysfunction in pre‐mature ejaculation patients

Abstract: We aimed to investigate of whether atypical masturbation behaviour is a pre‐disposing factor in ED aetiology in pre‐mature ejaculation (PE) patients. In addition to demographic data, self‐estimated intravaginal ejaculatory latency time (IELT) was prospectively questioned in 2,572 patients between the ages of 18 and 60 who applied with the complaint of pre‐mature ejaculation between March 2018 and May 2020. The masturbation habits of the patients were questioned with open‐ended questions. After the exclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…These behaviors do not mimic real sexual experience. It mostly manifests itself as masturbation by lying on the bed in the prone position without using lubricant, rubbing the penis on the bed or pillow, and pressing it with the hands or rubbing it over the clothes 15 . In patients which we described as TMS in this study, frequently detected sexual dysfunctions are sexual reluctance, anorgasmia, ejaculatory dysfunction, and ED.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…These behaviors do not mimic real sexual experience. It mostly manifests itself as masturbation by lying on the bed in the prone position without using lubricant, rubbing the penis on the bed or pillow, and pressing it with the hands or rubbing it over the clothes 15 . In patients which we described as TMS in this study, frequently detected sexual dysfunctions are sexual reluctance, anorgasmia, ejaculatory dysfunction, and ED.…”
Section: Introductionmentioning
confidence: 78%
“…They also found that men with less frequency of vaginal sex had a higher rate of masturbation than those with more vaginal sex 23 . In similar studies conducted on men with sexual dysfunction, 15,24–26 the frequency of masturbation and possible predisposing factors were investigated and the rate of masturbation was found to be between 53% and 88% in the last 1 month period. In addition, the authors concluded that questioning masturbation is an important topic for understanding patients' general sexual attitudes and behaviors.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations